INFLUENCE OF CARIES AND ORAL HEALTH STATUS ON THE PREVALENCE OF DENTAL EROSION IN 7-14-YEAR-OLD-CHILDREN IN TURKEY - Elif Korkmaz; Arife Kaptan (Cumhuriyet University, 2020)
Aim: To determine the prevalence of erosion of schoolchildren, and to reveal the relationship between the dental caries, gingival health statuses, dental plaque levels and dental erosion. Materials and methods: A cross-sectional analysis was performed on a representative sample of 473 children (aged 7─14 years). The O'Sullivan, Decayed-Missing-Filled (DMF), Plaque, and Gingival indices were used during the examination of the children. The values were evaluated using chi-square test, Tukey's test, and multivariate logistic regression analysis. Results: Dental erosion was observed in 21.8% of the children. Lesions were mostly observed in the enamel but less than a half of the buccal surface was affected. Erosion was found to be statistically higher in older children (p=0.001). There was no statistically significant relationship between the children's sexes and erosion (p=0.157). A higher level of erosion was observed in children with high DMFT and DMFS values and low dft and dfs values (p<0.05); children with dental erosion had higher plaque and gingival indices (p<0.05). Conclusion: Though limited to the enamel, the prevalence of erosion was high and was associated with age, dental caries, dental plaque, and gingival inflammation.